Correlation between VCT controlled estimates and VDT slopes. - Ariana Youm (22676310) (2025)
VCT = Verbal Completion Task; VDT = Verbal Discrimination Task. There were no significant correlations between controlled estimates from the VCT and similarity slopes from the VDT in either younger or older adults. (TIFF)